2012
DOI: 10.1007/s13691-012-0022-5
|View full text |Cite
|
Sign up to set email alerts
|

Cancer risk and management in a woman with Peutz-Jeghers syndrome

Abstract: Peutz-Jeghers syndrome (PJS) is known to cause an elevated risk of cancer development. We present the case of a 41-year-old Japanese woman with PJS who had various lesions in the abdominal and pelvic organs. The preoperative diagnosis was a right ovarian tumor suspected to be a mucinous borderline tumor, a uterine cervical lesion suspected to be lobular endocervical glandular hyperplasia (LEGH), gastrointestinal hamartomatous polyps, and intestinal invagination. She underwent hysterectomy, right salpingo-oopho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…A search of the PubMed database using the keywords 'Peutz-Jeghers syndrome' and 'lobular endocervical glandular hyperplasia' revealed that there have been four case reports on PJS with LEGH. [5][6][7][8] Two of these were diagnosed by hysterectomy 6,8 and one by simple trachelectomy. 5 In the fourth case, conization was performed and the patient was followed for 12 months, but no recurrence was noted.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A search of the PubMed database using the keywords 'Peutz-Jeghers syndrome' and 'lobular endocervical glandular hyperplasia' revealed that there have been four case reports on PJS with LEGH. [5][6][7][8] Two of these were diagnosed by hysterectomy 6,8 and one by simple trachelectomy. 5 In the fourth case, conization was performed and the patient was followed for 12 months, but no recurrence was noted.…”
Section: Discussionmentioning
confidence: 99%
“…Reportedly, MDA develops in 15–30% of PJS patients, and about 10% of MDA patients have PJS . However, there have been only a few reports of PJS patients complicated by LEGH; to our knowledge, only four cases have been reported . As the lesions of LEGH and MDA tend to be present near the internal os, hysterectomy, not conization of the cervix, is necessary to diagnose these accurately.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation